Measures of human capital: A review of the literature - Trinh Le; John Gibson; Les Oxley (New Zealand Government, The Treasury, 2005)
Human capital is increasingly believed to play an important role in the growth process, however, adequately measuring its stock remains controversial. This paper identifies three general approaches to human capital measurement; cost-based, income-based and education-based, and presents a critical review of the theories and their applications to data from a range of countries. Emphasis on empirical evidence will be given to the case of New Zealand.
Keywords: C52; F43; N10; O41; 330; human capital; economic growth